ANALISIS CASHFLOW{ARm KAS) SEBAGAI SUMBER INFORMASI BAGI SERIKAT PEKERJA DI WILAYAH KABUPATEN/KOTA BEKASI - Diana Fajarwati (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2007)
Statement of cash flows is the financial statement that provides information about the cash in flows and out flows from operating, investing, and financing activities during an accounting. The informatiom provided in a statement of cash flows, if used with related disclosures and the other financial statements, should help investors, creditors, and other to:l) Assess the enterprise’s ability to generate positive future net cash flows, 2) Assess the enterprise’s ability to meet its obligations, its ability to pay dividends, and its needs for external financing, 3) Assess the reasons for differences between net income and (associated cash receipts and payments, 4) Assess the effects on an enterprise’s financial position of both its cash and noncash investing and financing transaction during a period.